Dehydroepiandrosterone increases in zone of glutamine synthetase-positive hepatocytes in female rat liver: a putative androgenic effect - Mayer, Doris; Bannasch, Peter (Histochemistry and cell biology, 1999)
The adrenal steroid dehydroepiandrosterone (DHEA) is a hepatocarcinogen and peroxisome proliferator in the rat, producing an increase in peroxisomes mainly in perivenular parts of the liver lobule.